Cost-effective synthesis and solution processing of porous polymer networks through methanesulfonic acid-mediated aldol triple condensation. (16th January 2018) - Guo, Zi-Hao; Wang, Chenxu; Zhang, Qiang; Che, Sai; Zhou, Hong-Cai; Fang, Lei
Abstract : A highly efficient aldol triple condensation method was developed for scalable synthesis and solution processing of conjugated porous polymer networks. Abstract : A highly efficient aldol triple condensation method was developed for scalable synthesis of conjugated porous polymer networks. This bottom-up strategy features inexpensive starting materials and reagents as well as simple reaction procedures, which are ideal for mass production of functional organic porous materials. The resultant porous material demonstrated quick and selective adsorption of organic small molecules in aqueous solution. In addition, the pristine composition of the reaction mixture enabled solution processing of these cross-linked porous materials through a "soaking–heating–washing" procedure to form composite membranes that are essential for practical applications.